A conceptual project of a device for human wrist functional rehabilitation - Lewandowski, Bogusz; Olinski, Michał; Wudarczyk, Sławomir; Gronowicz, Antoni (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, the problems of devices supporting functional rehabilitation of a human wrist were addressed. A literature review and a description of selected devices together with an indication of their advantages and disadvantages were conducted. The biomechanical structure of a human wrist was analyzed. On this basis and after taking into consideration ranges of motion of the selected joints the concept of a new mechanism was developed. A 3D model of the device was built in the Autodesk Inventor system. For the purpose of simulations another model was developed in the MSC Adams system. Issues of drives and sensors selection, as well as requirements for the control system, were examined.
Keywords: rehabilitation support; robotic-assisted treatment; wrist rehabilitation